Sofia Valdez, future prez - Beaty, Andrea (Beaty, Andrea. Questioneers., 2019)
When her abuelo is injured at the local landfill, second-grader Sofia is determined to transform the dangerous Mount Trashmore into a park, taking on City Hall in the process.